Underwriter Reputation and IPO Underpricing: The Moderating Role of The Listing Board in The Indonesia Capital Market - Kuswandi, Brillian Arbianto; Lubis, Arief Wibisono; Viverita, Viverita (Universitas Proklamasi 45, 2025)
It is widely believed that the underwriter affects the IPO performance of the issuing firm. This research investigates how the reputation of underwriters influences the initial returns of IPOs, considering the moderating effect of the listing board. This study focuses on the data from 305 IPO Companies between 2018 and 2023. This data is being analyzed using an Independent Sample t-test and Ordinary Least Squares (OLS) regression analysis. The study finds that IPOs underwritten by prestigious underwriters typically experience lower underpricing, attributable to the underwriters’ ability to reduce information asymmetry and select higher-quality issuers.